Challenges in The Management of Kallmann Syndrome : A Case Report - Saiful Anam; R. Bowo Pramono (PP PERKENI, 2025)
Kallman syndrome is combined disorder of hypogonadotropic hypogonadism and anosmia. Incidence of congenital hypogonadotropic hypogonadism is 1-10:100,000 live births, and approximately 2/3 and 1/3 of cases are caused by Kallmann syndrome and idiopathic hypogonadotropic hypogonadism, respectively. We report a man, 35 years old, with complaints of small penis, small voice, impaired smell, gynecomastia, narrowing of visual field, mustache not growing, little pubic and armpit hair. Patient underwent surgery on both breasts with histopathological results of gynecomastia, no malignancy. Testicular ultrasound results showed bilateral testicular atrophy. Laboratory results showed karyotype 46XY, Follicle-stimulating hormone 1.79 mIU/mL, Luteinizing hormone 1.49 mIU/mL, testosterone <0.03 ng/mL, estradiol 5.0 pg/mL, prolactin 6.75 ng/mL and prostate-specific antigen 0.473 ng/mL. Head CT scan imaging showed bilateral otitis media, mastoiditis and sinusitis. Patient was diagnosed Kallmann syndrome, anxiety and depression symptoms (ADS) chronic tubotympanic suppurative otitis media, sinusitis, oculus dexter and sinister hemianopsia. Patient was treated with testosterone undecanoate injection 1000 mg IM every 3 months, levofloxacin 500 mg PO once daily, avamys nasal spray twice daily. Symptoms of Kallman syndrome can include absent or incomplete pubertal development, anosmia or hyposmia, and low sex steroid levels. KAL1 gene mutations cause Gonadotropin-releasing hormone (GnRH) deficiency, associated with Kallmann syndrome. Testosteron replacement is indicated for men who already have children or have no desire for children. Surgery should be considered as the last option in patients with considerable discomfort, psychological stress, cosmetic problems, long‑standing gynecomastia (>12 months) and suspected malignancy. The aim of testosterone therapy is to reverse the symptoms of hypogonadism, and surgery is last option in patients with considerable discomfort.